Advancing understanding of dietary and movement behaviours in an Asian population through real-time monitoring: Protocol of the Continuous Observations of Behavioural Risk Factors in Asia study (COBRA) - Edney, Sarah Martine (SAGE PUBLICATIONS LTD, 2022)
10.1177/20552076221110534